Adobe Animate Classroom in a Book (2020 release) - Chun, Russell (Classroom in a book., 2020)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Animate choose Adobe Animate Classroom in a Book (2020 release) from Adobe Press. The 11 project-based step-by-step lessons in this book show users the key techniques for working in Animate. Adobe Animate provides more expressive tools, powerful controls for animation, and robust support for playback across a wide variety of platforms. Create interactive virtual reality immersive environments with VR 360 and VR Panorama documents. Gain advanced control over character animations with layer parenting and AI-driven lip syncing. Learn to create dynamic strokes with the new fluid brush, and work smarter with the revamped Timeline, Tools palette and Properties inspector. Support for SVG, WebGL, HTML5, animated GIFs, and HD video, and seamless collaboration with other designers and with other Adobe applications through Creative Cloud libraries make Adobe Animate the ideal development environment for creative animation and multimedia. Classroom in a Book is the best-selling series of hands-on software training books designed to help you learn the features of Adobe software quickly and easily. Developed by the training experts at Adobe Systems, these books offer complete, self-paced lessons designed to fit your busy schedule and help you learn the features of Adobe software quickly and easily. The online companion files include all the necessary assets for students to complete the projects featured in each chapter as well as eBook updates when Adobe releases new features for Creative Cloud customers. And all buyers of the book get full access to the Web Edition: a Web-based version of the complete eBook enhanced with video and interactive multiple-choice quizzes.